Analysis of the Role of Infrastructure and Transportation in the Development of Batam City - Adi, Pramono; Sidabutar, Yuanita FD; Suciati, Herlina (Pusat Studi Pembangunan dan Pemberdayaan, 2025)
Batam City is a city known as the gateway to free trade in Indonesia, continuing to improve itself from time to time. A number of strategic infrastructure projects were then worked on to encourage economic growth, and increase Batam's competitiveness with regions in Indonesia and other countries such as Malaysia and Singapore. Historically, various supporting infrastructures have been built since this area was developed as an industrial area. Starting from highways, ports, to airports that were deliberately built to attract investment. However, the massive development of Batam now also demands development according to the times. The results of this study are used to analyze how infrastructure and transportation can contribute to the development of Batam City from an economic, social, and environmental perspective. With a qualitative approach and SWOT analysis, this study evaluates the influence of government policies, private investment, and the influence of infrastructure development on the competitiveness of Batam City. The results of the study show that investment in road, port, and airport infrastructure has increased connectivity that can drive the city's economic growth globally. The sustainable and competitive growth of Batam City requires a more targeted strategy in the development of infrastructure and transportation. The use of data-based technology such as GIS can help in more accurate planning, while the integration of public transportation systems will increase efficiency and comfort for the community.